2019
DOI: 10.2217/epi-2018-0153
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation of Shelf, Shore and Open Sea CpG Positions Distinguish High Microsatellite Instability from Low or Stable Microsatellite Status Colon Cancer Stem Cells

Abstract: Aim: To investigate the genome-wide methylation of genetically characterized colorectal cancer stem cell (CR-CSC) lines. Materials & methods: Eight CR-CSC lines were isolated from primary colorectal cancer (CRC) tissues, cultured and characterized for aneuploidy, mutational status of CRC-related genes and microsatellite instability (MSI). Genome-wide DNA methylation was assessed by MethylationEPIC microarray. Results: We describe a distinctive methylation pattern that is maintained following in vivo passag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 74 publications
6
19
0
Order By: Relevance
“…The CpG clusters can be identified as ‘islands’, ‘shores’, ‘seas’ and ‘shelves’. 60 CpG islands are defined as 1 kb regions of high CpG density, usually found near promoters; shores are within the 2 kb sequence neighboring the islands with seas and shelves being flanked further from shores, with occurrence of CpGs decreasing in density the further away from the island it is. 60 …”
Section: Resultsmentioning
confidence: 99%
“…The CpG clusters can be identified as ‘islands’, ‘shores’, ‘seas’ and ‘shelves’. 60 CpG islands are defined as 1 kb regions of high CpG density, usually found near promoters; shores are within the 2 kb sequence neighboring the islands with seas and shelves being flanked further from shores, with occurrence of CpGs decreasing in density the further away from the island it is. 60 …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, unlike MSS CRCs, MSI-high CRCs showed a much better response to immune checkpoint inhibitors (42,43). More recently, several MSI-like gene expression signatures were also proposed with likewise controversial signi cance (18,44,45). Our data suggest that the 12-genes hypermethylated cohort of mCRCs is characterized by a MSI-like phenotype and that the methylation pro le of the 12-genes signature may represent an alternative strategy to better de ne a subgroup of mCRCs with a CIMP-H status and a MSIlike phenotype, characterized by a poor clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular mechanisms, including advanced glycation end product (AGE) [10], aberrant glycosylation [11], abnormal telomerase activity [12], unfolded protein response (UPR) [13], angiogenesis [14], reactive oxygen species (ROS) production [15], epithelial-mesenchymal transition (EMT) [16], cell apoptosis, proliferation, survival, migration, invasion, self-renewal, differentiation and dedifferentiation reprogramming, are altered to survive host defense or therapeutic insults. However, the dysregulation of these molecular mechanisms may not explain CRC origins and development, suggesting that various genetic and epigenetic events occur at the gene level [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the interaction of these pathways is precise and complicated. In addition, a growing body of research shows that genetic perturbation or epigenetic dysregulation can promote the development of CRC or that the cancer itself can provoke genetic perturbation or epigenetic dysregulation [18]. Vdovikova et al found that bacteria can target host cell epigenetics to promote carcinogenesis in HCT8 cells [31].…”
Section: Introductionmentioning
confidence: 99%